Collins grammar for IELTS - Aish, Fiona (Collins English for exams., 2012)
Grammar for IELTS is a self-study course for learners of English who plan to take the Academic IELTS test to demonstrate that they have the required ability to communicate effectively in English at university. Twenty 4-page units each target one section of the IELTS test.